The Effect of Creative Writing Activities on the Story Writing Skill In University Curriculum - Alwasilah, Senny Suzanna (Journal of Education Research, 2024)
This study explores the effectiveness of structured guidance and visual stimuli in enhancing college students' creative writing skills. Following a phased approach grounded in scholarly recommendations, students were guided through narrative text structure, free topic writing, and visual prompt utilization. The introduction of structured narrative elements facilitated comprehension and provided a framework for students to build upon. Additionally, brainstorming sessions and group discussions helped students overcome initial uncertainties and generate ideas. Visual prompts proved invaluable in stimulating creativity and providing a scaffold for story development. By applying Tredinnick's (2006) guidance, students produced well-structured narratives with engaging plots and character development. Overall, this study underscores the importance of incorporating structured guidance and visual aids in creative writing instruction to foster students' confidence and proficiency in narrative composition.